2020
DOI: 10.1364/boe.383390
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation of lymphatic drainage and clearance: perspective strategy for augmentation of meningeal lymphatic functions

Abstract: There is a hypothesis that augmentation of the drainage and clearing function of the meningeal lymphatic vessels (MLVs) might be a promising therapeutic target for preventing neurological diseases. Here we investigate mechanisms of photobiomodulation (PBM, 1267 nm) of lymphatic drainage and clearance. Our results obtained at optical coherence tomography (OCT) give strong evidence that low PBM doses (5 and 10 J/cm 2 ) stimulate drainage function of the lymphatic vessels via vasodilation (OCT data on the mesente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 31 publications
3
79
0
1
Order By: Relevance
“…As reported in our previous studies of PS-mediated stimulation of meningeal lymphatic clearance and drainage function, the 1267-nm laser in a dose of 9-10 J/cm 2 (17 min of laser irradiation, 5-min pause, 61 min in total) is effective for lymphatic clearance of small and large molecules from the brain into dcLNs [33, 34, 39]. Based on our pervious animal data and the established PS protocol [33, 34, 39], we investigated the effect of PS on MLVs using a 1267-nm laser with an indicated above dose. We uncovered that although IVH seemed to widen the diameter distribution of MLVs, it didn’t make significant difference on the average diameter (25.8±18.2 μm vs 25.75±15.7 μm).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…As reported in our previous studies of PS-mediated stimulation of meningeal lymphatic clearance and drainage function, the 1267-nm laser in a dose of 9-10 J/cm 2 (17 min of laser irradiation, 5-min pause, 61 min in total) is effective for lymphatic clearance of small and large molecules from the brain into dcLNs [33, 34, 39]. Based on our pervious animal data and the established PS protocol [33, 34, 39], we investigated the effect of PS on MLVs using a 1267-nm laser with an indicated above dose. We uncovered that although IVH seemed to widen the diameter distribution of MLVs, it didn’t make significant difference on the average diameter (25.8±18.2 μm vs 25.75±15.7 μm).…”
Section: Resultsmentioning
confidence: 91%
“…The PS-mediated stimulation of the lymphatic drainage and clearing function might be one mechanisms playing an important role of PS in neurorehabilitation [32]. It has been proved that PS can regulate the relaxation and permeability of the mesenteric lymphatic vessels, activate moving of immune cells in the lymph, and has effectiveness in the management of lymphedema [33][34][35]. In our preliminary work, we clearly demonstrated that the near-infrared PS (1267 nm) stimulates clearance of tracers from the brain via MLVs after opening of the blood-brain barrier (BBB) or after its intracerebral injection [33,34,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated possible mechanisms of tPS-stimulation of lymphatic drainage and clearance [88], [89]. Our results demonstrate that already low PS doses (1267 nm, 5 and 10 J/cm 2 ) cause relaxation of the mesenteric LVs and increase their permeability to fluorescent macrophages via a decrease of expression of the tight junction proteins and the transendothelial resistance.…”
Section: Photostimulation Of the Lymphatic Systemmentioning
confidence: 85%
“…However the detection of the lymphatic perfusion is not a trivial procedure that currently can be performed only with very specific animal models like the rat intestine mesentery lymphatic [88], [89] or the mouse ear skin [165]- [170], but no label-free detection of the lymph flow through MLVs has been reported yet. Both of these models represent the peripheral lymphatic system and provide the advantage of intravital optical imaging of the LVs structure and function [161], [168].…”
Section: Measurement Of the Lymph Flowmentioning
confidence: 99%